Tipped out: How do gratuities affect restaurant operations?. Issue 4 (8th August 2017) - McAdams, Bruce; von Massow, Michael
ABSTRACT: Tipping is a well-established social norm in North American restaurants. Researchers have given considerable attention to the interaction between consumers and servers, but less so to the relationships within a restaurant and even less so to restaurant managers' perspectives. Our study, the first of its kind, used interviews and a survey to explore the perspectives of both restaurant managers and servers in identifying operational issues arising from tipping. Inequity and unfairness, loss of control of service quality, and difficulties in succession planning and promotion were identified. There is clearly a need to investigate strategies to mitigate some of these impacts.